Resistensi dan Negosiasi Tubuh: Studi Sosiologi Gender terhadap Prajurit KOWAD Senior (40+ Tahun) dalam Mempertahankan Eksistensi Keolahragaan di Lingkungan Militer - Nur Hidayah; Farizha Irmawati; Rubbi Kurniawan; Eko Sulistiono; Tri Asih Wahyu Hartati (Universitas Hamzanwadi, 2026)
Military institutions establish uncompromising physical standards as a prerequisite for professionalism. For senior female soldiers of the Army Women's Corps (KOWAD) aged 40 years and above, this demand conflicts with natural biological degradation and pre-menopausal transition. This study aims to explore the lived experiences of senior KOWAD in interpreting physical activities and to analyze their negotiation strategies in maintaining symbolic capital within the military environment. Using a qualitative phenomenological approach, this study involved 17 active soldiers ranging from Senior Non-Commissioned Officers to Junior Officers through purposive sampling. Data were collected through in-depth interviews and observations, then analyzed thematically using the theoretical lenses of Bourdieu, Goffman, and Foucault. The findings reveal four negotiation dimensions body and aging the application of pragmatic embodiment as health risk management, professionalism the conversion of fitness into symbolic capital for leadership legitimacy, role negotiation the use of role linkage to balance family burdens (sandwich generation), and resistance the rejection of the domestication of the